Poles Apart: The Processing and Consequences of Mixed Media Stereotypes of Older Workers. (6th October 2016) - Kroon, Anne C.; van Selm, Martine; ter Hoeven, Claartje L.; Vliegenthart, Rens
Abstract : This study uses the Stereotype Content Model to examine how mixed‐media stereotypes about older workers affect the implicit activation and application of competence and warmth stereotypes among employees. By means of a 2 × 2 experiment, we show that a newspaper article portraying older workers in a stereotypical manner (i.e., high rather than low in warmth, low rather than high in competence) inhibits and evokes negative employability perceptions, resulting in a net negative effect on intentions to hire an older worker. Findings indicate that mixed‐media portrayals have stronger effects on implicit stereotype activation compared to stereotype application. We propose a tailored media‐based stereotype reduction strategy, whereby the negative component of older workers' stereotypes is replaced by stereotype‐disconfirming information.